Lycium barbarum Polysaccharides Promote Maturity of Murine Dendritic Cells through Toll-Like Receptor 4-Erk1/2-Blimp1 Signaling Pathway - Xiangguo Duan; Yaru Lan; Xiaoyu Zhang; Shaozhang Hou; Jian Chen; Bin Ma; Yuhan Xia; Chunxia Su (Journal of Immunology Research)
In previous studies, Lycium barbarum polysaccharides (LBP), a traditional Chinese medicine, can promote immature dendritic cells (DCs) to mature. However, the molecular mechanisms by which LBP works are not yet elucidated. Here, we found that LBP can induce DCs maturation, which is mainly characterized by the upregulation of MHCII and costimulatory molecules (CD80, CD86), and increase the production of IL-6 and IL-4. Furthermore, we found that LBP could increase the mRNA and protein expression of TLR4, p38, Erk1/2, JNK, and Blimp1 signal molecules. More interestingly, after blocking by Toll-like receptor 4 inhibitor, Resatorvid (TAK 242), the mRNA and protein expression of TLR4, Erk1/2, and Blimp1 was significantly decreased while the expression of p38 and JNK has not changed. Then, we found that after blocking by p38 inhibitor (SB203580), Erk inhibitor (PD98059), and JNK inhibitor (SP603580) separately, Blimp1 protein expression was significantly reduced; after downregulating Blimp1 by Blimp1-siRNA, the production of IL-6 was reduced. In conclusion, our results indicate that LBP can induce maturation of DCs through the TLR4-Erk1/2-Blimp1 signal pathway instead of the JNK/p38-Blimp1 pathway. Our findings may provide a novel evidence for understanding the molecular mechanisms of LBP on activating murine DCs.